The Influence of Financial Distress, Auditor Switching, Profitability, Audit Quality on Audit Delay - Windy Permatasari; Cahyati, Ari Dewi (Future Science, 2024)
Audit delay is the period for completing the annual financial report audit, namely from the date the company's books are closed to the date stated in the independent auditor's report. The length of the audit delay affects the value of the audited financial statements. This research aims to find out whether Financial Distress, Auditor Switching, Profitability, and Audit Quality affect Audit Delay. The data used in this research is secondary data in the form of audited financial reports. This research population was obtained using methods from non-cyclical consumer sector companies listed on the IDX during the 2020-2022 period. Based on predetermined criteria, a sample of 129 companies was obtained. The analytical method used is multiple linear regression analysis with the STATA 17 software tool. The research results show that financial distress affects audit delay. Meanwhile, auditor switching, profitability, and audit quality do not affect audit delay.